2020
DOI: 10.31533/pubvet.v14n4a549.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity in Danio rerio exposed to increasing concentrations of soluble fractioning of burnt soybean oil biodiesel

Abstract: The objective of this research, to determine the presence of micronuclei in erythrocytes of juvenile fish zebrafish (Danio rerio) exposed to increasing soluble fraction concentrations of burnt soybean oil biodiesel (FSB). The fishes (N=15) were placed in polyethylene aquariums, with constant aeration, and submitted to acute toxicity test in a completely randomized design, with six treatments and two replicates. The treatments consisted of different FSB concentrations: solution I (control), solution II (0.0645 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The micronucleus tests were conducted following Al-Sabti et al 1995), using blood on clean, labeled slides. The frequency of micronuclei was determined based on the method proposed by Carrasco et al (1990) and Oliveira et al (2020). Once stained, the slides were visualized under an immersion optical microscope at a magnification of 1000 × .…”
Section: Collection and Preparation Of The Samplesmentioning
confidence: 99%
“…The micronucleus tests were conducted following Al-Sabti et al 1995), using blood on clean, labeled slides. The frequency of micronuclei was determined based on the method proposed by Carrasco et al (1990) and Oliveira et al (2020). Once stained, the slides were visualized under an immersion optical microscope at a magnification of 1000 × .…”
Section: Collection and Preparation Of The Samplesmentioning
confidence: 99%
“…The frequency of micronuclei was determined based on the method proposed by Carrasco et al (1990) and Oliveira et al (2020), which considers only intact cells, and de nes micronuclei based on the following four criteria: 1) features that are less than one third the size of the nucleus; 2) in the same focal plane as the nucleus; 3) chromatin coloration and structure identical to those of the nucleus, and 4) no link with the principal nucleus. In addition to the presence of micronuclei, the nuclear abnormalities present in the cells were described, counted, and classi ed following Carrasco et al (1990) as: (1) blebbed (nucleus with a minor evagination of the nuclear membrane with euchromatin or heterochromatin); (2) lobed (nucleus with larger and more ample evagination than the blebbed cells); ( 3) vacuolated (nucleus containing vacuoles) or ( 4) notched (nucleus well de ned morphologically).…”
Section: Collection and Preparation Of The Samplesmentioning
confidence: 99%
“…The potentially harmful effects of many substances found in aquatic environments have been the focus of an ample range of research due to the potential consequences for both aquatic organisms and human beings (Costa et al, 2008;Ghisi et al, 2010;Martins and Costa et al, 2015;Rocha et al, 2016;Oliveira, et al, 2020;Santana, 2020), given that many of the pollutants discharged directly or indirectly into these environments originate from human activities and, while some substances being biodegradable, many others are not (Robert, 2008). A number of other studies have also shown that the degradation of the aquatic ecosystems exposed to industrial waste may lead to a decline in the abundance of commerciallyimportant sh species, resulting in social and economic problems for the local communities (Kennish, 1985;Blaber, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The micronucleus tests were conducted following Al-Sabti & Metcalfe (1995), using blood on clean, labeled slides. The frequency of micronuclei was determined based on the method proposed by Carrasco et al (1990) and Oliveira et al (2020). Once stained, the slides were visualized under an immersion optical microscope at a magni cation of 1000x.…”
Section: Collection and Preparation Of The Samplesmentioning
confidence: 99%